THE ROLE OF EXAGERATION IN LINGUISTIC REFLECTION OF THE WORLD'S VIEW - Komilova Gulmira Temirovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article examines all the features of the genre of hyperbole. We will talk about the creation of subtleties of meaning and we will try to explain exaggeration and the world scene through linguistic description and examples from artistic works.